(untitled) (Journal of the College of Basic Education, 2022)
The study, tagged with technical variables and their reflections in the design system of the industrial product, dealt with many concepts and ideas that divided the field for the multiplicity of technical variables and their design trends in the South Korean car products of the company (Kia).